2014
DOI: 10.1590/s0100-736x2014001100006
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação por Ipomoea asarifolia em bovinos e ovinos no Rio Grande do Norte

Abstract: Ipomoea asarifolia é uma das principais plantas tóxicas para ruminantes nas regiões Norte e Nordeste. A intoxicação ocorre na época das secas quando há escassez de forragem e é mais frequente em ovinos do que em outras espécies, porem casos espontâneos também são relatados em caprinos, bovinos e búfalos. Este trabalho relata a ocorrência de 18 surtos de intoxicação em bovinos por I. asarifolia que ocorreram de agosto de 2012 a fevereiro de 2013 no estado do Rio Grande Norte. De um total de 1704 bovinos, 202 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
5
0
3
Order By: Relevance
“…One of the fundamental points to be determined in this report was whether I. pes caprae causes storage disease or a condition compatible with that described in so-called tremorgenic syndromes. The absence of storage, confirmed by histopathological analysis and lectin-histochemical evaluation, indicates that I. pes caprae is responsible for a tremorgenic picture similar to those described in cases of Ipomoea asarifolia (Döbereiner et al 1960, Riet-Correa et al 2003, Araújo et al 2004, Barbosa et al 2005.…”
Section: Discussionmentioning
confidence: 55%
“…One of the fundamental points to be determined in this report was whether I. pes caprae causes storage disease or a condition compatible with that described in so-called tremorgenic syndromes. The absence of storage, confirmed by histopathological analysis and lectin-histochemical evaluation, indicates that I. pes caprae is responsible for a tremorgenic picture similar to those described in cases of Ipomoea asarifolia (Döbereiner et al 1960, Riet-Correa et al 2003, Araújo et al 2004, Barbosa et al 2005.…”
Section: Discussionmentioning
confidence: 55%
“…Other neurological poisonous plants, such as Ipomoea spp. and Solanum paniculatum are endemic in northeastern Brazil and should be considerate in the differential diagnosis (Antoniassi et al 2007, Guaraná et al 2011, Carvalho et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Ipomoea asarifolia (Convolvulaceae) is found in the whole country, but the intoxication has been reported in sheep, goats, cattle, and buffalo in the northeastern region and on Marajó Island in the state of Pará. The disease occurs during the dry season when there is shortage of forage , Carvalho et al 2014a). Lambs are more frequently affected.…”
Section: Tremorgenic Plants: Ipomoea Asarifolia Chloris Virgata Chlmentioning
confidence: 99%
“…Lambs are more frequently affected. It has been demonstrated that the toxic compound is eliminated by milk affecting nursing lambs that are maintained confined while their mothers ingest I. asarifolia but do not show clinical signs themselves (Carvalho et al 2014a. The disease also occurs in nursing calves and lambs that remain confined while their mothers are in the field ingesting I. asarifolia (Carvalho et al 2014c).…”
Section: Tremorgenic Plants: Ipomoea Asarifolia Chloris Virgata Chlmentioning
confidence: 99%